Agent-Based Modeling for Archaeologists: Part 1 of 3. Issue 2 (22nd May 2019) - Romanowska, Iza; Crabtree, Stefani A.; Harris, Kathryn; Davies, Benjamin
ABSTRACT: Formal models of past human societies informed by archaeological research have a high potential for shaping some of the most topical current debates. Agent-based models, which emphasize how actions by individuals combine to produce global patterns, provide a convenient framework for developing quantitative models of historical social processes. However, being derived from computer science, the method remains largely specialized in archaeology. In this paper and the associated tutorial, we provide a jargon-free introduction to the technique, its potential and limits as well as its diverse applications in archaeology and beyond. We discuss the epistemological rationale of using computational modeling and simulation, classify types of models, and give an overview of the main concepts behind agent-based modeling. Abstract : Modelos cuantitativos robustos de sociedades humanas en el pasado tienen el potencial de informar los temas de debate actual, particularmente modelos informados por estudios de arqueología. Modelos basados en sistemas multiagente proveen un marco práctico para explorar modelos cuantitativos de sociedades en el pasado. Aun así, al ser un método de informática no es aún bien establecido entre la mayoría de arqueólogos. En este artículo y el tutorial que lo acompaña, proveemos una introducción a estos métodos, libres de jerga técnica, su potencial y sus límites, y también las diversas aplicaciones en arqueología. Además, discutimos la epistemología de utilizar modelos computacionales y de simulación, clasificamos los tipos de modelos, y proveemos un resumen de los conceptos principales de los modelos multiagente.